2015
DOI: 10.1002/joe.21625
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Work and Family Obligations in Pakistan and the Netherlands: A Comparative Study

Abstract: A study of 486 banking employees in Pakistan and the Netherlands investigated the effect of work‐family conflict on psychological contract breach of work‐family balance obligations. The results showed that 127 Dutch respondents were more likely to experience work interference with family than employees in Pakistan, despite the fact that Pakistanis have longer working hours than their Dutch counterparts. The relationship between family overload and work interference with family, however, was stronger among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
(64 reference statements)
0
16
0
Order By: Relevance
“…This clearly tempers the theoretical progression in the area. Nonetheless, empirical results have generally supported the notion that the work demands-WF constructs link is stronger in individualistic versus collectivistic countries (e.g., Jin et al, 2013 with work-family conflict;Spector et al, 2004;Spector et al, 2007;Syed et al, 2015), although two studies found the opposite pattern (Jin et al, 2013 with work-to-family enrichment;Yang et al, 2000).…”
Section: Cross-cultural Hypotheses and Theoretical Rationalementioning
confidence: 92%
See 4 more Smart Citations
“…This clearly tempers the theoretical progression in the area. Nonetheless, empirical results have generally supported the notion that the work demands-WF constructs link is stronger in individualistic versus collectivistic countries (e.g., Jin et al, 2013 with work-family conflict;Spector et al, 2004;Spector et al, 2007;Syed et al, 2015), although two studies found the opposite pattern (Jin et al, 2013 with work-to-family enrichment;Yang et al, 2000).…”
Section: Cross-cultural Hypotheses and Theoretical Rationalementioning
confidence: 92%
“…-Collectivism (vs. individualism) moderates the relationship between work demands and work-to-family conflict such that the relationship is weaker in more collectivistic cultures because: o In collectivistic cultures work is viewed as a means to enhance family well-being and therefore work demands are not likely to be interpreted in a way that leads to work-to-family conflict (Aycan, 2008;Lu et al, 2006;Spector et al, 2004;Spector et al, 2007;Syed et al, 2015). o The large amount of family support available in collectivistic cultures serves as a buffer so that work demands have less of an impact on work-to-family conflict (Jin et al, 2013;Spector et al, 2007).…”
Section: Work Demandsmentioning
confidence: 99%
See 3 more Smart Citations